73.1k views
2 votes
Solve: 9x - 18 = 3(3x - 2) - 12 A) x = 2 B) x = 1 2 C) x = −3 D) infinitely many solutions

User MShekow
by
5.9k points

2 Answers

6 votes
your answer is C
because 3(3x-2) is 9x-6 now and -12 is 9x-18 so in the end its 9x-18=9x-18 so -18 + -18 is -36 and 9 * -3 is -36 so therefore your answer is C
User Joshua Mire
by
6.7k points
4 votes
the answer should be D) because 9x-18=3(3x-2)-12 using pemdas distribute into parenthesis first gives you (9x-6)-12 then combine like terms and get
9x-18 = 9x-18
User Chris Bartow
by
6.0k points